Establishment of the first sharia-compliant human milk bank: The IIUM experience in developing Halimatussaadia mother’s milk centre - Jamani, Nurjasmine Aida; Ismail, Hamizah; Daud, Normadiah; Syed Abd Hamid, Syed Abdul Khaliq; Ali, Zurina; Barnett, Debbie (2021)
Human milk has been recommended as the best and gold standard in infant feeding in terms of nutritional and immunological value including donor human milk. Donor human milk has gained demandin the recent years when mother own’s milk is not available. There has been an increasing number of human milk banks around the world especially in Southeast Asia. This is to aid in donor milk collection, processing and distribution of a safe donor human milk. In contrast to this development, Muslim countries are still in debate in developing a sharia compliant human milk bank in view of concerns from Fiqh perspectives especially in milk kinship. We share our journey and challenges faced in developing and establishing “Halimatussaadia Mother’s Milk Centre” at Sultan Ahmad Shah Medical Centre @IIUM, the first Sharia-compliant human milk bank in Malaysia.